Pembelajaran dan Sistem Pengajaran Bahasa Arab di Madrasah Ibtidaiyah: Inovasi atau Tantangan - Fathoni Fathoni (MODELING: Jurnal Program Studi PGMI, 2021)
Without learning Arabic, science and Islamic teachings will be difficult to know and apply properly. The success of learning Arabic can also occur if the teacher has the right method in learning. The purpose of this study is to improve Arabic in madrasah Ibtidaiyah/elementary schools which must be prepared so that children can speak Arabic with four language skills that are taught integrally, namely listening, speaking, reading and writing. Even so, at the basic education level (MI/SD) the focus is more on simple listening and speaking skills as the basis for language. The method in this study uses a qualitative method with the type of descriptive analytic research. The results in this study that the use of various methods in the teaching and learning process of Arabic is very dependent on the principles and concepts understood by the teacher of the language. In addition, a method is also very closely related to other aspects of learning, both traditional and modern (innovative) methods.